2012
DOI: 10.3174/ajnr.a2941
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Reduction in Temporal Bone CT with Iterative Reconstruction Technique

Abstract: BACKGROUND AND PURPOSE:Iterative reconstruction of CT images is characterized by reduced image noise and may allow reduction in radiation exposure. We investigated the influence of an IRT technique on image quality and radiation dose savings when applied to temporal bone CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…This is probably one of the factors behind reports of "unnatural" image texture in IR compared with FBP [16,21]. Compared with FBP, the shape of the NPS curves was least affected by Philips iDOSE* of all the evaluated algorithms.…”
Section: Noise Power Spectrummentioning
confidence: 81%
“…This is probably one of the factors behind reports of "unnatural" image texture in IR compared with FBP [16,21]. Compared with FBP, the shape of the NPS curves was least affected by Philips iDOSE* of all the evaluated algorithms.…”
Section: Noise Power Spectrummentioning
confidence: 81%
“…SAFIRE utilization in cervical spine CT has resulted in better depiction of the intervertebral disks and ligaments (59,60). Fine bone structures, such as the temporal bone or paranasal sinuses, often necessitate thinner section reconstructions that are subject to increased noise secondary to quantum mottle; again, this has shown to be an area in which the noisereduction properties of IR techniques may be put to good use (61,62). ASIR has been shown to enhance the delineation between white and gray matter (63).…”
Section: Head and Neckmentioning
confidence: 98%
“…6 Iterative reconstruction has the potential to reduce image noise and radiation dose compared with standard filtered back-projection reconstruction algorithms in many studies, [14][15][16][17] including in the temporal bone. 13 The amount of dose reduction highly depends on the specific vendor, scanner platform and imaging task. Dose reduction in this study was a combination of these 2 techniques, similar to that demonstrated in the previous phantom studies by comparing filtered back-projection-zUHR, IR-zUHR, and IR-UHR.…”
Section: Discussionmentioning
confidence: 99%
“…8 A recent focus of CT imaging has been to reduce patient exposure to ionizing radiation, following the as low as reasonably achievable principle. [9][10][11][12][13] However, the consequent reduction in photons can adversely affect image quality and present a great challenge when imaging small, anatomically complex structures embedded in attenuating bone, such as those of the middle and inner ear. Iterative reconstruction (IR) is a promising reconstruction technique that is superior to standard filtered back-projection reconstructions and theoretically can be used to improve resolution at standard radiation doses or to maintain current resolution by using a reduced radiation dose.…”
mentioning
confidence: 99%